2017
DOI: 10.1002/ajh.24756
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognostic factors in multiple myeloma patients with light chain deposition disease

Abstract: Light chain deposition disease (LCDD) is characterized by monotypic immunoglobulin depositions which will eventually lead to loss of organ function if left untreated. While the kidney is almost always affected, the presence and degree of LCDD in other organs vary. Ten to thirty percent of LCDD patients have underlying Multiple Myeloma (MM), yet outcome and prognostic markers in this particular patient group are still lacking. Here, we analyzed 69 patients with MM and biopsy proven LCDD and report on renal and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
1
29
2
2
Order By: Relevance
“…Haematological response was reported in the study using the borrowed 2006 International Myeloma Working Group (IMWG) response criteria for myeloma (Durie et al, 2006). Twelve individual patients achieved ≥VGPR during the study and although no effect of haematological response on RS was detected, previous studies have demonstrated that achieving excellent haematological response in MGRS patients is associated with an improved RS (Sayed et al, 2015;Kourelis et al, 2016;Mohan et al, 2017). Importantly, there are no existing MGRS response criteria and the multiple myeloma response criteria do not include renal response as part of the response measures.…”
Section: Discussionmentioning
confidence: 99%
“…Haematological response was reported in the study using the borrowed 2006 International Myeloma Working Group (IMWG) response criteria for myeloma (Durie et al, 2006). Twelve individual patients achieved ≥VGPR during the study and although no effect of haematological response on RS was detected, previous studies have demonstrated that achieving excellent haematological response in MGRS patients is associated with an improved RS (Sayed et al, 2015;Kourelis et al, 2016;Mohan et al, 2017). Importantly, there are no existing MGRS response criteria and the multiple myeloma response criteria do not include renal response as part of the response measures.…”
Section: Discussionmentioning
confidence: 99%
“…High‐dose chemotherapy and ASCT still remains one of the frontline treatments of MM . ASCT is associated with a transplant‐related mortality of 1%‐10% . The risk of infection is highest during pre‐engraftment phase which is associated with neutropenia and mucositis …”
Section: Introductionmentioning
confidence: 99%
“…1 ASCT is associated with a transplant-related mortality of 1%-10%. 5 The risk of infection is highest during pre-engraftment phase which is associated with neutropenia and mucositis. 6 The microbial etiology of febrile neutropenia has changed over the past several decades.…”
Section: Introductionmentioning
confidence: 99%
“…18 Patients with LCDD may have coexistent MM (10%-30%) and AL amyloidosis (17%). 19 Light chain deposition disease with cardiac involvement (33%) has overall poor survival and is related to increased transplant-related mortality. Only 18% of patients had LV ejection fraction less than 50%, and most frequent manifestations are atrial arrhythmias, sinus bradycardia, and diastolic dysfunction.…”
Section: Casementioning
confidence: 99%